2020
DOI: 10.1038/s42003-020-0780-0
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM study of an archaeal 30S initiation complex gives insights into evolution of translation initiation

Abstract: Archaeal translation initiation occurs within a macromolecular complex containing the small ribosomal subunit (30S) bound to mRNA, initiation factors aIF1, aIF1A and the ternary complex aIF2:GDPNP:Met-tRNA i Met. Here, we determine the cryo-EM structure of a 30S: mRNA:aIF1A:aIF2:GTP:Met-tRNA i Met complex from Pyrococcus abyssi at 3.2 Å resolution. It highlights archaeal features in ribosomal proteins and rRNA modifications. We find an aS21 protein, at the location of eS21 in eukaryotic ribosomes. Moreover, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
95
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(101 citation statements)
references
References 101 publications
(170 reference statements)
5
95
1
Order By: Relevance
“…However, several studies have also shown that loss of some particular rRNA modifications leads to diverse negative effects: severe growth retardation [30], slower rates and accuracy of translation [31], alterations of active sites [32], and a decrease in the fidelity of translation initiation [33]. Due to recent advances in X‐ray crystallography [2,8] and single‐particle electron [34,35] cryo‐EM, structural biology techniques have become efficient methods for verification rRNA modifications. Exceptional scientific rigor should be taken to cross‐validate with biochemical and bioinformatics data if available to ensure that errors do not occur.…”
mentioning
confidence: 99%
“…However, several studies have also shown that loss of some particular rRNA modifications leads to diverse negative effects: severe growth retardation [30], slower rates and accuracy of translation [31], alterations of active sites [32], and a decrease in the fidelity of translation initiation [33]. Due to recent advances in X‐ray crystallography [2,8] and single‐particle electron [34,35] cryo‐EM, structural biology techniques have become efficient methods for verification rRNA modifications. Exceptional scientific rigor should be taken to cross‐validate with biochemical and bioinformatics data if available to ensure that errors do not occur.…”
mentioning
confidence: 99%
“…No r-proteins found only in the archaeal and bacterial domains are found. One protein that could be specific of the archaeal domain found in place of eukaryotic eS21 and, therefore, named aS21 was identified recently in the SSU of Pyrococcus abyssi (Coureux et al, 2020) and Thermococcus celer (Nurenberg-Goloub et al, 2020). However, further phylogenetic studies are required to firmly determine whether the protein is unique to archaea or distantly related to eS21.…”
Section: The Archaeal Ribosome Is Of the Eukaryotic Typementioning
confidence: 99%
“…The number of universal (u), eukaryotic (e), bacterial (b), archaeal (a) -type ribosomal protein is indicated. One protein possibly specific to archaea (a) has recently been identified in P. abyssi (Coureux et al, 2020;Nurenberg-Goloub et al, 2020).…”
Section: The Archaeal Ribosome Is Of the Eukaryotic Typementioning
confidence: 99%
See 2 more Smart Citations